Implementation of Project-Based Learning Model with Digital Flipbook Media in Story Texts Learning - Uswatun, Imroatin; Kurniati, Endang (JTP - Jurnal Teknologi Pendidikan, 2024)
One of the factors that cause low ability in reading and writing Javanese legend text is learning models and media are less varied. The project-based learning model with digital flipbook media assistance felt appropriate as an alternative for overcoming problems reading and writing legendary stories text at SMP Negeri 3 Semarang. This study aimed to describe the different results and students' performance between experimental classes that use the project-based learning model with control class without the model and media for student class VIII SMP Negeri 3 Semarang in elements reading and writing story. This study used experimental research with a true experimental design in the form posttest-only control design. Data collection techniques used tests techniques, observations, and interviews. Data analysis was performed using quantitative description techniques with SPSS Statistic 26 and qualitative description techniques. The results showed that learning outcomes and performance of students experimental class were better than a control class. Differences in learning outcomes can be seen from the average of reading and writing in control class amounting to 75,39 and the average in experimental class amounting to 81,92. Apart from that, using this model can improve students performance namely, students are more active, enthusiastic, disciplined with time, and have good responsibility. In conclusion, these models and media can be implemented by Javanese language teachers to optimize student learning outcomes and performance.